Influence of dietary mulberry (Morus alba L.) leaf supplementation on production performance, blood metabolites, rumen fermentation characteristics and ruminal bacteria community in lactating dairy cows - Patipan Hnokaew; Korawan Sringarm; Phongsakorn Chuammitri; Chaiwat Arjin; Chompunut Lumsangkul; Supamit Mekchay; Apinya Satsook; Yulei Wang; Paramintra Vinitchaikul (Italian Journal of Animal Science)
The purpose of this study was to determine the effect of mulberry (Morus alba L.) leaf (ML) supplementation on the productivity, blood metabolism, rumen fermentation characteristics and rumen microbial population in lactating dairy cows. Twelve healthy multiparous Holstein dairy cows (initial characteristics: body weight = 442.83 ± 86.87 kg; milk yield = 12.55 ± 1.91 kg/d; days in milk = 150.0 ± 47.0 d) were randomly allocated to two treatment groups of six cows each. The cows were fed two different diets: a control diet (basal diet without ML; CTRL group) and a ML-supplemented diet (basal diet + 300 g ML; ML group). The trial lasted for a total of 28 d after an adjustment period of 14 d. The total rumen volatile fatty acid (VFA) levels (p = .063) and the propionate level (p < .05) were increased in the ML group, whereas the ratio of acetate to propionate was significantly decreased (p < .05). A microbiome study demonstrated that the dietary treatments significantly influenced the composition of rumen bacteria. The ruminal populations of Paludibacter propionicigenes, Ruminococcus sp. JE7A12 and Prevotella oris were greater (p < .05) in ML group than in CTRL group, while Enterococcus faecalis numbers significantly decreased (p < .05) in the ML group. Supplementing a dairy cow diet with 300 g ML has the potential to alter the microbial community and fermentation in the rumen, leading to an increase in propionate synthesis.